Caracterización numérica del comportamiento del fluido térmico de un sistema típico de "mangos de caja" que trabaja en un escenario de tratamiento de agua caliente - Mendoza Orbegoso, Elder Marino (2018)
The mango is one of the most popular and profitable tropical fruits in international markets. In Peru, mango exportation is regulated within a quality control phytosanitary framework that eliminates the " fruit fly" (Ceratitis Capitata) as the main requirement for exportation. This is the reason why mangos must undergo a hot-water treatment, which involves the immersion of the fruit into hot water in which the temperature and immersion time is regulated by the phytosanitary protocols of the importing country.This paper is oriented towards the characterization of the thermal and fluidynamic behavior of the “crate-mango” system used in the hot-water treatment of the mango. This is done in order to identify the main operational conditions associated with processing the fruit in the shortest possible time, thereby reducing operational costs. Such characterization was developed by the use of tools based on numeric simulations, as a way of identifying the transient behavior of mangos submitted to the hot-water treatment. Consequently, a crate-mango system involving immersion of the fruit in a constant flow of hot water at 47°C was simulated for the purpose of determining the velocity range of hot water that allows the reduction of the mango processing time.The results obtained through the use of the simulations found that hot water flows with velocities between the range of 0.05 and 0.3 m/s are recommended for the effective hot-water treatment of the mango. This velocity range represents an appropriate engagement between low processing times and low mechanical power consumption in terms of the propellers required for hot water circulation.